Characterization of TPO Enzyme and its Immunogenecity in New Zealand White Rabbits (Oryctolagus cuniculus) - Devi Ramadani; Andreas Budi Wijaya; Arie Srihardyastutie; Dyah Kinasih Wuragil; Rulli Rosandi; Achmad Rudijanto; Aulanni'am Aulanni'am (Postgraduate, University of Mataram, 2024)
Hypothyroidism is characterized by inadequate production of thyroid hormones, chiefly thyroxine (T4) and triiodothyronine (T3). Thyroid peroxidase (TPO), is an enzyme and crucial for producing thyroid hormones, and also serves as a primary autoantigen in autoimmune thyroid conditions, such as Hashimoto's thyroiditis and Graves' disease. The existence of anti-thyroid peroxidase antibodies (anti-TPO) indicates an autoimmune response in which the immune system TPO which is normally recognized as part of the body (self), begins to be identified by the immune system as a something foreign (non-self). This study aimed to characterize, measure TPO activity, and evaluate the immunogenicity of TPO protein derived from patient serum and its ability to induce TPO antibody production in New Zealand White Rabbits. TPO protein isolation was achieved through SDS-PAGE and confirmed by western blot technique have molecular weight of 52 kDa. In samples from normal patients, the average TPO enzyme activity was 31.34 U/mL, while in hypothyroid patients, the average activity increased to 49.46 U/mL. TPO polyclonal antibody production in rabbits indicated its immunogenicity, peaking in week eight post-immunization, with an ELISA absorbance of 0.555. Dot blot analysis further confirmed anti-TPO sensitivity at various dilutions, anti-TPO has a high sensitivity at 1:80 dilution still detects TPO in sera patient.